UNDERSTANDING OF THE BENEFITS AND VALUE OF GOODS AND ITS EFFECT ON STUDENT CREATIVITY IN UTILIZING USED GOODS: MINDSET OF STUDENT ENTERPRENEUR - Dicki Hartanto; Yulisyah Fitriana; Sri Yuliani (UIR Press, 2021)
This study discusses the effect of the material benefits and value of an item on student creativity in utilizing used goods. This study aims to determine how much the influence of material benefits and values ​​on students' creativity in utilizing used goods at SMAN 1 Salo, Kampar Regency. This research was conducted at Salo 1 State Senior High School, Kampar Regency, with 57 students as the subject. This research was conducted from 19 July - 9 September 2013, with data collection techniques through tests, questionnaires (questionnaires) and documentation, while the object of this research is the material benefits and value of an item, and students' creativity in utilizing used goods. Based on the results of data analysis, it can be concluded that the material benefits and value of an item have a significant influence on students' creativity in utilizing used goods. This can be seen from the r count Product Moment which is greater than r table both from the significant level of 5% and 1% (0.250 <0.450> 0.325). Associated with the entrepreneurial mindset in an effort to encourage entrepreneurs who come from the younger generation, our educational curriculum must instill in students the potential for entrepreneurship.